Situation in Special Education: Interaction between Teachers and Children Who Have Intellectual Disability and Who Display Challenging Behaviours - Guikas, Ioanna; Morin, Diane (Canadian Journal of Education/Revue canadienne de l'éducation, 2021)
Interactions between staff and individuals with intellectual disability have been shown to influence the development or maintenance of challenging behaviours among the latter. Given the implications of these observations, the present study sought to describe special education teachers’ responses to challenging behaviours displayed by their pupils. Eight teachers and 12 children with intellectual disability who manifested challenging behaviours were observed over the course of 6 months. Teachers completed questionnaires regarding their emotional reactions to, and understanding of, challenging behaviours. They also reported their behavioural and emotional responses to challenging behaviours described in vignettes. The combination of observation and questionnaires provided a more comprehensive understanding of teacher’s attitudes towards challenging behaviours. Results indicated a discrepancy between reported and observed behaviours. Teachers preferred verbal interventions or not responding to challenging behaviours. The analysis of interactions between teachers and their pupils highlighted relationships between emotions, attributions and several behaviours.